Alamat ng tipaklong The legend of the grasshopper - Matias, Segundo D.; Tejido, Jomike; Bravo, Becky; Garcia, Edith (Quezon City Lampara Publishing House, Inc., 2011)
"In the old days, there was a boy named Paklong who dreamed of living in the palace. Destiny made his dream come true--he became the friend of the prince, the king and the queen; he got invited to the place, and was given the prince's clothes to wear. if only Paklong remained humble despite the good fortune that came his way, his dream of becoming a true prince could have been fulfilled."
Stories with moral values
Text in Filipino and English.
Keywords: Grasshoppers -- Fiction